Pengembangan “MAMOLA KIDS” Berbasis QR Sebagai Stimulasi Kemampuan Motorik Halus Pada Anak Usia 5-6 Tahun - Ima Miftaku Ra'uf; Pramono Pramono; Munaisra Tri Tirtaningsih (Universitas Muhammadiyah Ponorogo, 2026)
This research and development project aims to create an educational media product called Mamola Kids—a QR-based smart book designed to stimulate fine motor skills in children aged 5 to 6 years. Initial findings revealed that several children exhibited underdeveloped fine motor abilities, such as difficulty tying shoelaces and writing. Moreover, classroom activities often lacked engaging media, making the learning process monotonous. The study employed a Research and Development (R&D) approach, specifically adopting the Synthesis (adaptive Pramono) development model. The feasibility evaluation of the Mamola Kids QR-based smart book resulted in a score of 85.00% from material experts, 88.33% from media experts, 96.25% in small group trials, and 97.03% in large group trials conducted in three kindergartens across Malang City. In conclusion, the QR-integrated Mamola Kids media proves to be highly suitable for enhancing fine motor skills in early childhood learning for 5–6-year-old children.